Iodine/persulfate-promoted site-selective direct thiolation of quinolones and uracils - Danupat Beukeaw (2020)
© 2019 Elsevier Ltd A simple and general method for direct thiolation of 4-quinolones with disulfides or thiols under I2/K2S2O8 system has been developed. Under the optimal conditions, the C–S bond coupling can take place effectively with good to decent yields and excellent regioselectivity of the S-linked products. The established metal-free site-selective approach was also applicable to transform a range of uracil substrates to the thio-substituted products under mild conditions. Further transformation to the sulfone derivatives can be conveniently performed in one-pot. These easy-to-handle protocols represent a useful and interesting synthetic alternative with good substrate scope and functional group compatibility.